Optimizing the Seed Rate for Maximized Yield And Benefits of Wheat Under Strip Tillage In Bangladesh (SAARC Journal of Agriculture, 2021)
An on-farm experiment was conducted at the farmer's field located at the Durbachara village of Gauriopur upazilla under the Mymensingh district of Bangladesh from November 2015 to March 2016 to study the effect of seed rate on yield performance of wheat under strip tillage. Wheat cv. BARI Gom-26 was sown under conventional tillage (CT) vs. strip tillage (ST), including four seeding rates viz. 100, 110, 120, and 130 kg ha-1. The CT was done with a two-wheel tractor and consisted of two primary tillages followed by two secondary tillages. The ST was done using a Versatile Multi-crop Planter (VMP) machine in a single pass process. A pre-plant herbicide, glyphosate was applied 3 days before of ST operation @ 3.7 L ha-1. The experiment was laid out in a randomized complete block design with four replications. The impact of tillage methods on the seed rate was found significant in the yield and economic profit of wheat. The longest spike with the highest number of grains spike-1, the highest weight of 1000-grain, grain yield, and BCR was recorded when 120 kg seeds of wheat sown with strip tillage. This practice produced a 25% higher yield and earned 51% higher profit than the practice of seeding 100 kg seeds ha-1 with conventional tillage.SAARC J. Agric., 19(1): 45-56 (2021)